(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The scheduled tribes (STs) are among the most disadvantaged groups in India. They have been dealing with problems for years. The primary issues facing tribes today include forest rights, land alienation, money-lender exploitation, mining, and tribal displacement. The construction of dams, motorways, mines, power plants, new cities, and industrial developments are all examples of development projects. According to the census of 2011, there were 10.43 crore individuals who identified as tribal, making up 8.6% of the population. 89.97% of people live in rural areas, while just 10.03% live in urban areas. Between the years covered by the Censuses of 2001 and 2011, the total population increased by 17.69%, while the tribal population increased by 23.66%. The population’s ratio of females to males is 940 per 1000, but it is 990 for the Scheduled Tribes. A significant number of Indian communities have been agriculturally based ever since ancient times. In the hilly regions of the North Eastern states, it requires competence. Even though it is widely practised, it has been recognized for a long time as one of India’s most significant issues with the development of its tribal communities. As a result, state governments have devised programs to wean people off of shifting agriculture. The degree to which their living conditions have improved due to the shift from nomadic to stationary agriculture is a significant query that has yet to be satisfactorily answered. A topic connected to this one is how the agrarian structure of the indigenous communities shifted when farming was settled. There have been two categories created for loans: hereditary and contracted. A loan that is inherited is called a hereditary loan. In other words, the present household members do not benefit from this debt, yet they are still required to pay it off. The present study is based on secondary data collected from various sources, including journals, periodicals, books, and websites